Sterility Preservation of Surgical Dressing Packs Wrapped in Gumstick Lining Material - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Post-sterilisation contamination is the ability of the organisms to penetrate through the wrapping material and settle on the enclosed instruments. Safeguarding the sterility of sterile dressing packs during transportation and storage is an important requirement of a sterile supply packaging system. We evaluated the use of locally available and affordable tailoring lining material popularly known as gumstick. The objective of this study was to ascertain the efficacy of gumstick lining material in safeguarding the sterility of wrapped surgical dressing instrument.Materials and Methods:The post-sterilisation sterility was confirmed by culturing the sterile packs and then exposed to contaminants by leaving the packs on a microbiology working bench. The wrapped packs were then contaminated with suspensions of control strains of some selected bacteria, then swabbed and cultured. The surgical packs were also exposed to environmental contaminants, swabbed and cultured.Results:All cultures yielded no growth proving that the wrapped surgical instruments are bacteriologically sterile and gumstick provides the needed protection against contamination of surgical packs.Conclusion:Gumstick lining material is therefore recommended as packaging material for surgical instrument particularly in resource-constrained settings.